Compound Heterozygous MRPS14 Variants Associated With Leigh Syndrome - Maria Gabriela Otero; Christina Freeman; Ruchi Shah; Renkui Bai; Hong Cui; Marian Castro; Zachary Myers; Eric Choy; Derek Chan; Molly Easter; Sophia Y. Zhao; Madeline Babros; et al. (Annals of Clinical and Translational Neurology)
ABSTRACT MRPS14 (uS14m) is a nuclear‐encoded ribosomal protein important for mitochondria‐specific translation. To date, only a single individual with a recessive MRPS14‐related disorder (also known as COXPD38) has been reported. We report an additional subject possessing novel compound heterozygous MRPS14 variants (p.Asp37Asn, p.Asn60Asp). The subject presented at 2 years with motor and language delays associated with elevated serum lactate/alanine levels. Brain MRI showed a constellation of signal abnormalities consistent with Leigh Syndrome, while MR spectroscopy had an increased lactate peak. Western blots of fibroblasts showed decreased MRPS14 and COX2 protein levels. These results support the pathogenicity of the MRPS14 variants identified here.